Endoscopic Management of Fronto-Ethmoidal Sinus Mucocele - Neupane, Yogesh; Basnet, Meenakshi; Pradhan, Bibhu (Nepalese Journal of ENT Head and Neck Surgery, 2014)
DOI: http://dx.doi.org/10.3126/njenthns.v3i2.10162 Nepalese Journal of Head and Neck Surgery Vol.3(2) 2012: 26-28